Les sciences mathématiques et physiques dans l’ancienne Université de Vilna (1579—1832) - Žemaitis, Z. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: З. Жемайтис. Физико-математические науки в старом Вильнюсском университете (1579—1832 гг.) Z. Žemaitis. Fizikos ir matematikos mokslai Vilniaus senajame universitete (1579—1832)